2007
DOI: 10.1007/978-1-59745-395-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tolerance by Adoptive Transfer of Treg Cells

Abstract: Naturally arising CD4+CD25+ regulatory T (Treg) cells can be exploited to establish immunologic tolerance to allogeneic transplants. In vivo exposure of CD4+CD25+ T cells from normal naive mice to alloantigen in a T cell-deficient environment elicits spontaneous expansion of alloantigen-specific CD4+CD25+ natural Treg cells, which are able to suppress allograft rejection mediated by subsequently transferred naive T cells, leading to long-term graft tolerance. Similar antigen-specific expansion of natural Treg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In [26] showed that, in addition to the suppression of proliferation by expanded T reg , a long-term transplant tolerance can be established in mice. Our study has shown that canine T reg could be characterized phenotypically by CD4, CD25 and FOXP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In [26] showed that, in addition to the suppression of proliferation by expanded T reg , a long-term transplant tolerance can be established in mice. Our study has shown that canine T reg could be characterized phenotypically by CD4, CD25 and FOXP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate the beneficial effects of Tregs in inducing tolerance in multiple autoimmune and inflammatory diseases such as cardiac fibrosis [195], bacteria induced sepsis [196], diabetes [197] and asthma [198]. Notably, in vitro expansion of Tregs followed by adoptive transfer has become an active area of research for autoimmune disease treatment [115]. However, such an approach requires knowledge of the specific target antigens to allow relevant epitope specific Tregs to be isolated.…”
Section: Promoting Immune Tolerance and Treg Cell Activitymentioning
confidence: 99%
“…Evidence from murine studies suggests that suppression mediated by cytokines is of particular importance at environmental interfaces, such as the gut, skin and lungs [106,112,113]. In autoimmunity, a lower frequency of Tregs is often observed in the active disease state [114,115]. Genetic deficiency in Treg production significantly increases the risk of autoimmune disease development [116].…”
Section: Deficient Function Of Regulatory T Cells In Alopecia Areatamentioning
confidence: 99%
“…The latter generated in the thymus have a stable suppressive function, while the former generated in the periphery or in vitro have an unstable or transient suppressive function. Adoptive transfer of iTregs prolongs and even prevents graft rejection in transplantation models [8,31,32]. Therefore, we monitored changes in in vitroinduced Tregs transferred from FoxP3 gfp mice to congenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs can suppress the proliferation and/or function of infiltrative T cells and relieve acute allorejection. Furthermore, Treg numbers are noted to have increased in a mouse model of transplant tolerance [7], and adoptive transfer of induced Tregs (iTregs) can relieve rejection of heart transplants in mice [8]. However, intragraft FoxP3 expression increases in cardiac allograft patients with acute rejection [9].…”
Section: Introductionmentioning
confidence: 99%